2007
DOI: 10.1007/s00264-007-0441-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome following excision of a tumour and reconstruction of the distal radius

Abstract: We retrospectively studied the functional and oncological results of 15 patients after reconstruction of the distal radius with osteoarticular allograft or non-vascularised fibular graft following wide excision of an aggressive benign or malignant tumour. Eight patients underwent osteoarticular allograft and seven patients had a non-vascularised autogenous fibular graft reconstruction. The average time for incorporation of the graft was 6 and 5 months in each reconstruction respectively. There was no tumour re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 27 publications
1
48
2
Order By: Relevance
“…Sheth et al [36] found comparable MSTS scores and grip strength when comparing intralesional excision and resection arthrodesis, respectively, for giant cell tumor of the distal radius in 26 patients. Some favorable functional results also have been reported for osteoarticular allograft reconstruction using proximal fibular autograft, however none were performed in our patients and there are concerns with high complication rates [1,3,6,23,24,26,31].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Sheth et al [36] found comparable MSTS scores and grip strength when comparing intralesional excision and resection arthrodesis, respectively, for giant cell tumor of the distal radius in 26 patients. Some favorable functional results also have been reported for osteoarticular allograft reconstruction using proximal fibular autograft, however none were performed in our patients and there are concerns with high complication rates [1,3,6,23,24,26,31].…”
Section: Discussionmentioning
confidence: 56%
“…McGough et al [28] reported 30% recurrence in 33 patients, Harness and Mankin [18] reported 42% recurrence in 26 patients, Sheth et al [36] reported 25% recurrence in 12 patients, and O'Donnell et al [30] reported 50% recurrence in 10 patients. Conversely, en bloc resection of the distal radius with either arthrodesis or osteoarticular allograft has reported low recurrence rates of 0% [1,4,5,13,19,31,36,39], with few studies showing recurrence in greater than 25% [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…The best treatment approach for GCTs that occur in the distal radius is unclear. Recurrence rates have ranged from 25% to 89% for both procedures [1,4,29,35,41], although the recurrence rates for en bloc resection reportedly range from 0% to 33% [1,3,29,41]. In addition, en bloc resection usually requires sacrifice of the articular surface, and secondary arthritis has occurred in 13% to 50% of patients [8,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction is challenging due to the high functional demands on the hand. Common reconstruction techniques include arthrodesis with different autografts [1, 59], prosthetic replacement [1013], ulnar translocation [5, 14], arthroplasty using (vascularised [8, 15] or nonvascularised [5, 1618]) autologous fibula graft, or osteoarticular allograft reconstructions (Figure 1) [5, 16, 17, 1925]. …”
Section: Introductionmentioning
confidence: 99%